A new and simple way to prepare monolithic solid oxide fuel cell stack by stereolithography 3D printing technology using 8 mol% yttria stabilized zirconia photocurable slurry. Issue 10 (August 2022) - Jia, Kaijie; Zheng, Lina; Liu, Wen; Zhang, Jinjin; Yu, Fangyong; Meng, Xiuxia; Li, Claudia; Sunarso, Jaka; Yang, Naitao
Abstract: Yttria (8 mol%) stabilized zirconia (8YSZ) photocurable slurry is the basis for stereolithography-based 3D (SLA) printed structured electrolyte support for monolithic solid oxide fuel cell (SOFC) stack. The curing resin with trifunctional trimethylolpropane triacrylate and 1, 6-hexanediol diacrylate (TMPTA/HDDA) mass ratio of 1.5:8.5 and 1 wt% of photoinitiator provided excellent curing performance and low viscosity of 2.1 mPa·s. Stable 8YSZ photocurable slurry possessing high solid content of 43 vol% and low viscosity of 3.6 Pa·s at 30 s −1 shear rate were obtained, without particle sedimentation after 180-day stability test. The activation energy of 8YSZ fabricated by 3D printing method was 0.87 eV, similar to that by dry-pressing method. The 3D printed monolithic 3-tube SOFC stack exhibited a peak power density of 230 mW·cm −2 at 850 °C. This research proves the great potential of 3D printing technology to prepare monolithic SOFC stack, paving the way to develop SOFCs for practical applications. Highlights: Give a new way to prepare monolithic SOFC stack with good performance. Obtain dense electrolyte supports for micro tubular monolithic SOFC stack. Provide a high solid loading 8YSZ photocuring slurry with low viscosity for SOFC. Develop a photocuring resin with enough cure depth and low viscosity for 3D printing.